Prompt-type frequency, auditory pattern discrimination, and EFL learners' production of WH-questions - Kim McDonough (2018)
Recently researchers have suggested that syntactic priming may facilitate the production of wh-questions with obligatory auxiliary verbs, particularly when learners are prompted to produce those questions with a wide variety of lexical items (McDonough & Kim, 2009; McDonough & Mackey, 2008). However, learners' ability to benefit from syntactic priming materials with prompt-type frequency may be mediated by their ability to recognize patterns in aural input. The purpose of this replication study is to confirm the positive impact of prompt-type frequency on learners' production of wh-questions reported by McDonough and Kim (2009), and to investigate whether its impact is mediated by learners' auditory pattern-discrimination abilities. Thai learners (n = 43) of English as a foreign language (EFL) carried out three oral tests, two sets of syntactic priming activities, and an auditory pattern-discrimination test over a 4-week period. Half of the learners carried out the syntactic priming activities with low-type-frequency prompts, whereas the other learners received high-type-frequency prompts. The results revealed a significant interaction between Type Frequency × Auditory Pattern Discrimination on the immediate and delayed posttests. The findings are discussed in terms of the potential role of individual cognitive factors in mediating the relationship between syntactic priming and second language (L2) development. Copyright © Cambridge University Press 2012.